Exploring the role and application of Sequency Ordered Hadamard Transform (SCHT) in quantum computing - Tian, Siming (Nanyang Technological University, 2022)
In quantum computing, Hadamard transform is applied to construct a quantum gate. The Sequency Ordered complex Hadamard Transform (SCHT) is proposed recently. In this project, we would like to explore the role and application of SCHT in Quantum Computing. We would go through what is Hadamard transform and SCHT. Then we will study the mechanism of quantum bit and quantum logic gate. Then, we would do a theoretical design of SCHT quantum logic gate and apply it using Qiskit, a quantum computing simulator. Finally, we would visualize the results and explore its distinctive characteristics.